1996
DOI: 10.4315/0362-028x-59.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase Inhibition of Fish Muscle Enzymes Using Legume Seed Extracts

Abstract: Seed extracts from indigenous and introduced legumes were prepared and used to search for inhibitors of fish muscle proteinases. Fish flesh extracts were prepared from samples of Merluccius productus (Pacific whiting or merluza) obtained off the Oregon coast and in the Gulf of California, respectively. The proteinase activity in the fish muscle for the Pacific whiting was the highest, followed by parasitized merluza. The lowest proteinase activity was for the nonparasitized merluza. Six out of 12 seed extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…Baker and Rackis (1986) reported that SPI might contain trypsin inhibitor activity as high as 40% of that found in raw soybeans. A 33‐kDa protein was presumed to be a Kunitz inhibitor whose molecular mass was reported to be more than 20 kDa under nonreducing condition by Garcia‐Carreno and others (1996).…”
Section: Resultsmentioning
confidence: 99%
“…Baker and Rackis (1986) reported that SPI might contain trypsin inhibitor activity as high as 40% of that found in raw soybeans. A 33‐kDa protein was presumed to be a Kunitz inhibitor whose molecular mass was reported to be more than 20 kDa under nonreducing condition by Garcia‐Carreno and others (1996).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition percentage of the alkaline proteolytic activity by the meals was quantified as in García-Carreño et al (1996). Briefly, for each activity unit (AU) of total alkaline proteases present in a volume of 20 ll of enzymatic extract 500 lg of meal extract were added and buffer pH 9.0.…”
Section: Fish Physiol Biochemmentioning
confidence: 99%
“…The LSPI extract from black cowpea seed generally showed higher stability than that from soybean seed. However, Garcia-Carreno et al 13 reported that the proteinase inhibitors from soybean seed were activated by heating. For the black cowpea seed extract the remaining activity was higher than 90% after heating at 80, 70 and 50°C for 10, 20 and 30 min respectively.…”
Section: Thermal and Ph Stability Of Lspi Extractsmentioning
confidence: 99%
“…12 Legumes contain inhibitors which can reduce proteinase activity in ®sh extracts. 13 The present investigation aimed to extract proteinase inhibitors from some Thai legume seeds and to study the inhibitory effects of the extracts on ®sh enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation